Diagnostic and Treatment-Related Challenges in Sinonasal Teratocarcinosarcoma: A Report of Three Cases - W. F. Julius Scheurleer; Weibel W. Braunius; Bernard M. Tijink; Luuk M. Janssen; Frank A. Pameijer; Gerben E. Breimer; Ernst J. Smid; Remco de Bree; Lot A. Devriese; Johannes A. Rijken (Case Reports in Otolaryngology)
Background. Sinonasal teratocarcinosarcoma is a rare, aggressive malignancy located almost exclusively in the nasal cavity, paranasal sinuses, or anterior skull base. Histopathological diagnosis can be challenging due to the heterogeneous composition. Methods. Retrospective analysis of 3 patients with sinonasal teratocarcinosarcoma diagnosed and treated at the University Medical Center Utrecht was conducted. Results. Patients presented with nasal obstruction, epistaxis, headaches, or behavioral changes. All three patients had locally advanced disease, and one had lymph node metastases. Two patients underwent surgery followed by radiotherapy, and one underwent neoadjuvant chemotherapy followed by surgery. The follow-up duration ranged from 3 to 32 months. All three patients died due to progression of their disease. Conclusion. Sinonasal teratocarcinosarcoma is characterized by rapid, aggressive local expansion. The prognosis is poor due to a high risk of metastases and locally recurrent disease. Multimodality treatment consisting of surgery, followed by (chemo)‐radiotherapy, is essential for optimizing outcomes. Neoadjuvant therapy offers a promising treatment option.